Effects of public investment on Ecuador’s economic growth - Chancusig, Gabriela (2022)
The research analyzes the effect of public investment on the economic growth of the provinces of Ecuador during the 2007-2017 period, which has been characterized by the strong emphasis on public expenditure channeled to the production sectors, strategic sectors, knowledge and human talent, social development, security and economic policy. This study includes the spatial factor to verify whether the geographical location of public investment had an impact on the economic growth of the ecuadorian provinces, using a Spatial Lag Model (SAR).The results show that there is a positive spatial dependence, where the capital allocated to the strategic and economic policy sector has become drivers of economic growth and reflect spatial spillovers in neighboring provinces.